Penamaan Desa di Kecamatan Kuantan Hilir Kabupaten Kuansing - Rijali Abdilla Zikhri; Yosi Septia Sari; Eva Ardila; Zaldi Aldika; Latif Latif (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2023)
Research on place names is very interesting to study. This is because the naming of places has a different background story. Research on place names can broaden social and cultural knowledge. Giving village names in Kuantan Hilir District, Kuansing Regency cannot be separated from natural elements and developing community stories. This research uses a descriptive method. The data in this study are the names of 15 villages in the Kuantan Hilir sub-district along with the history of the village based on the results of interviews and documents found. The problem that will be answered in this study is to describe the naming of villages in Kuantan Hilir District. After doing the analysis, it was found that the naming of villages in Kuantan Hilir District, Kuansing Regency was dominated by stories of developing people.